2004
DOI: 10.1002/polb.20247
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐interpenetrating polymer networks composed of poly(N‐isopropyl acrylamide) and polyacrylamide hydrogels

Abstract: Three series of semi‐interpenetrating polymer networks, based on crosslinked poly(N‐isopropyl acrylamide) (PNIPA) and 1 wt % nonionic or ionic (cationic and anionic) linear polyacrylamide (PAAm), were synthesized to improve the mechanical properties of PNIPA gels. The effect of the incorporation of linear polymers into responsive networks on the temperature‐induced transition, swelling behavior, and mechanical properties was studied. Polymer networks with four different crosslinking densities were prepared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 58 publications
(55 reference statements)
0
26
0
1
Order By: Relevance
“…For instance HEMA-gelatin gels reach strengths of 65 kPa, just slightly above gelatin alone [64] and polyacrylamide/poly-N-isopropylacrylamide IPN gels reach strengths of just 10 kPa [65]. Templating gels on a colloidal crystal and then removing the colloid has also been reported to give good toughness, although the modulus and strength remain low [66].…”
Section: Pamps-paammentioning
confidence: 99%
“…For instance HEMA-gelatin gels reach strengths of 65 kPa, just slightly above gelatin alone [64] and polyacrylamide/poly-N-isopropylacrylamide IPN gels reach strengths of just 10 kPa [65]. Templating gels on a colloidal crystal and then removing the colloid has also been reported to give good toughness, although the modulus and strength remain low [66].…”
Section: Pamps-paammentioning
confidence: 99%
“…Young's modulus was found to be slightly dependent on the temperature however the cross-linker concentration presented a strong influence. Semi-interpenetrating polymer networks were synthesized to improve the mechanical properties of NIPA gels [9] . These networks reinforced with cationic and nonionic PAAm exhibited higher tensile strength and elongations at break than NIPA hydrogels, whereas the presence of anionic PAAm caused a reduction in the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…There were some experimental publications investigating the effect of comonomer type and concentration on the properties of the hydrogels. It was shown that the cationic and anionic linear polyacrylamide (PAAm) could increase the swelling rate of the hydrogels, whereas nonionic PAAm diminished it . The swelling/deswelling performance and drug release could also be improved by increasing the amount of comonomer .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the cationic and anionic linear polyacrylamide (PAAm) could increase the swelling rate of the hydrogels, whereas nonionic PAAm diminished it. [8] The swelling/ deswelling performance and drug release could also be improved by increasing the amount of comonomer. [9] The concentration and type of cross-linker were also known to be the important factors in preparation of the semi-IPN hydrogels.…”
Section: Introductionmentioning
confidence: 99%